THE SOCIAL CONSTRUCTION OF DIGITAL REALITY: A CRITICAL REINTERPRETATION OF ONLINE INTERACTION IN CONTEMPORARY NETWORKED SOCIETIES - Riinawati Riinawati (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2025)
The rapid expansion of digital technologies has fundamentally transformed the ways individuals perceive, construct, and negotiate reality. This study critically examines the social construction of digital reality through online interactions, emphasizing how meaning is collaboratively produced in networked environments. Drawing upon social constructionism and critical digital theory, the article explores how platforms, algorithms, and user practices shape subjective and collective realities. The study employs a descriptive qualitative approach, synthesizing existing literature and conceptual analysis to reinterpret online interaction beyond surface-level communication. The findings reveal that digital reality is not merely a reflection of offline experiences but a distinct, layered construct shaped by technological affordances, algorithmic mediation, and socio-cultural contexts. Online identities are fluid and performative, often strategically curated to align with platform norms and audience expectations. Furthermore, power structures embedded in digital infrastructures influence what is visible, credible, and legitimate, thereby shaping knowledge production and social norms. This paper also highlights the paradox of digital interaction: while it enables democratized participation and global connectivity, it simultaneously reinforces echo chambers, misinformation, and surveillance practices. The reinterpretation proposed in this study positions digital interaction as an active site of meaning negotiation rather than passive consumption. Ultimately, this research contributes to a deeper understanding of how digital realities are constructed, contested, and institutionalized. It calls for a more critical awareness of the socio-technical mechanisms that underpin online interactions and encourages interdisciplinary approaches to studying digital societies in the contemporary era.